Adding cystatin C to the GRACE scale improves the prediction of bleeding complications in non-invasively treated patients with acute coronary syndrome - M. S. Kharchenko; A. D. Erlikh; E. I. Kosenkov; V. P. Masenko; N. A. Gratsianskyi (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the prognostic performance of the GRACE scale extended by cystatin C levels in the prediction of ischemic and hemorrhagic in-hospital complications among patients with acute coronary syndrome (ACS). Material and methods. In 160 ACS patients, admitted to the Moscow City Clinical Hospital No. 29 and included in the hospital register, blood levels of cystatin C were measured within the first 24 hours from admission. All patients were treated conservatively. The in-hospital risk of mortality and bleeding was assessed. The cut-off level of cystatin C was 1,53 mg/l. Results. High levels of cystatin C, high GRACE scale risk, and their combination were associated with a significant increase in the in-hospital risk of hemorrhagic and ischemic complications. Independent mortality predictors included GRACE levels (odds ratio, OR, 1,05; 95% confidence interval (CI) 1,02-1,08; p=0,002) and cystatin C levels (OR 1,01; 95% CI 1,00-1,02: p=0,025). Major and moderate bleeding complications were independently predicted by fibrinolysis (OR 9,86; 95% CI 1,74-55,20; p=0,01), leukocyte levels (OR 1,34; 95% CI 1,11-1,62: p=0,002), and haemoglobin levels (OR 0,96; 95% CI 0,91-0,99; p=0,043), as well as the combination of high GRACE risk levels and elevated cystatin C levels (OR 11,78; 95% CI 1,95-71,06; p=0,007). Adding cystatin C to the high GRACE risk improved the prognostic specificity by approximately 20% and did not affect the prognostic sensitivity in the prediction of in-hospital risk of major and moderate bleeding complications. Conclusion. The combination of high GRACE risk levels and elevated cystatin C levels was an independent predictor of major and moderate in-hospital bleeding complications, but not in-hospital death. Adding cystatin C to the GRACE scale by approximately 20% increased its specificity for the prediction of in-hospital risk of major and moderate bleeding complications.